An intact bony tympanic facial canal does not protect from secondary facial paresis in adult acute otitis media. Issue 5 (19th May 2020) - Meerwein, C; Pazahr, S; Stadler, T M; Nierobisch, N; Dalbert, A; Huber, A; Röösli, C
Abstract: Objective: To investigate the prevalence of bony dehiscence in the tympanic facial canal in patients with acute otitis media with facial paresis compared to those without facial paresis. Method: A retrospective case–control study was conducted on acute otitis media patients with facial paresis undergoing high-resolution temporal bone computed tomography. Results: Forty-eight patients were included (24 per group). Definitive determination of the presence of a bony dehiscence was possible in 44 out of 48 patients (91.7 per cent). Prevalence of bony dehiscence in acute otitis media patients with facial paresis was not different from that in acute otitis media patients without facial paresis ( p = 0.21). Presence of a bony dehiscence was associated with a positive predictive value of 66.7 per cent in regard to development of facial paresis. However, an intact bony tympanic facial canal did not prevent facial paresis in 44.8 per cent of cases (95 per cent confidence interval = 34.6–55.6). Conclusion: Prevalence of bony dehiscence in acute otitis media patients with facial paresis did not differ from that in acute otitis media patients without facial paresis. An intact tympanic bony facial canal does not protect from facial paresis development.